The Influence of Airborne Lead (Pb) and Individual Characteristics on Subjective Complaints Among Petrol Station Operators in Surabaya: A Cross-Sectional Study - Salsabila Ro'iqoh; Rusmiati Rusmiati; Winarko Winarko; Khambali Khambali; Seow Ta Wee (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Lead (Pb) is an air pollutant present in particulate form, often known as metallic powder. Gas station operators are one of the groups at risk of exposure to lead from motor vehicle emissions, which is harmful to health because it can accumulate in the body. This study aims to analyse the effect of airborne lead (Pb) and individual characteristics on the subjective complaints of petrol station operators in Surabaya. This study is an analytical observational study with a cross-sectional approach with a sample size of 28 respondents. Data were collected through measurements, observations and interviews, which were then processed and analysed using chi-square test. The results showed that airborne Pb measurements at two points met the NAB based on Permenaker No. 5 of 2018, which is less than 0.05 mg/m3. Based on the chi-square test, it was found that the variables of working time and the habit of using PPE had an effect on subjective complaints with a p-value <0.05. The variables airborne Pb, age and smoking habits had no effect on subjective complaints.